Aqueous- and solid-phase molybdenum geochemistry of oil sands fluid petroleum coke deposits, Alberta, Canada. (February 2019) - Robertson, Jared M.; Nesbitt, Jake A.; Lindsay, Matthew B.J.
Abstract: Fluid petroleum coke generated at oil sands operations in the Athabasca Oil Sands Region of northern Alberta, Canada, contains elevated concentrations of molybdenum (Mo) and other metals including nickel (Ni) and vanadium (V). Solid-phase Mo concentrations in fluid petroleum coke are typically 10 to 100 times lower than V and Ni, yet dissolved Mo concentrations in associated pore waters are often comparable with these metals. We collected pore water and solids from fluid petroleum coke deposits in the AOSR to examine geochemical controls on Mo mobility. Dissolved Mo concentrations increased with depth below the water table, reaching maxima of 1.4–2.2 mg L −1, within a mixing zone between slightly acidic and oxic meteoric water and mildly alkaline and anoxic oil sands process-affected water (OSPW). Dissolved Mo concentrations decreased slightly with depth below the mixing zone. X-ray absorption spectroscopy revealed that Mo(VI) and Mo(IV) species were present in coke solids. The Mo(VI) occurred as tetrahedrally coordinated MoO4 2− adsorbed via inner- and outer-sphere complexation, and was coordinated in an environment similar to Fe-(hydr)oxide surface complexes. The OSPW likely promoted desorption of outer-sphere Mo(VI) complexes, resulting in higher dissolved Mo concentrations in the mixing zone. The principal Mo(IV) species was MoS2, which originated as a catalyst added upstream of the fluid coking process. Although MoS2 is likely stable under anoxic conditions below the mixing zone, oxidative weathering in the presence of meteoric water may promote long-term Mo release. Graphical abstract: Highlights: Elevated Mo concentrations in oil sands petroleum coke are an environmental concern. Solid-phase Mo includes inner and outer sphere MoO4 2− complexes and MoS2. Aqueous Mo concentrations increase with pH and electrical conductivity. Outer-sphere MoO4 2− surface complexes are readily mobilized as conditions change. Results provide new insight into geochemical controls on Mo mobility in coke deposits.